ANALISIS KAPABILITAS, KOMUNIKASI INTERNAL, DAN IKLIM ORGANISASI TERHADAP KREATIVITAS SDM DALAM MENINGKATKAN KINERJA KARYAWAN DI PT ATOM JAYA MAKMUR KOTA TANGERANG - Juhaeri Juhaeri; Hamsinah Hamsinah; Ali Zaenal (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This thesis research aims to test and analyze the Analysis of Capability, Internal Communication, and Organizational Climate on HR Creativity in Improving Employee Performance at PT Atom Jaya Makmur Kota Tangerang. The type of research used is associative quantitative. The research population uses 217 companies registered with the company PT Atom Jaya Makmur Kota Tangerang. The sampling process uses simple random sampling, are obtained which are used in this study. The research data is then processed using Smart PLS 4 Software. The analysis method used is Outer Loading Factor showing that in each indicator, the outerloading factor has a value> 0.70, Convergent Validity shows a value greater than 0.70 that each variable statement is valid. The Coefficient of Determination test on the Performance model shows an R-square value of 0.745 which means that the contribution of Capability, Internal Communication and Organizational Climate to HR Creativity is 74.5% while the remaining 25.5% is a contribution from other variables outside the study. The significance test for capability (X1) showed a T-statistic of 7.617, greater than 1.96, and a P-value of 0.000, less than 0.05. The significance of the relationship between internal communication (X2) was supported by a T-statistic of 5.458, greater than 1.96, and a P-value of 0.002. The relationship between organizational climate (X3) was significant, with a T-statistic of 4.443, greater than 1.96, and a P-value of 0.000. The relationship between performance (Z) and HR creativity (Y) was significant, with a T-statistic of 5.142, greater than 1.96, and a P-value of 0.002. The measurement results for each variable indicated a significant influence of each variable on performance. Therefore, the study, entitled